Peculiarities of the Self-Concept of Students of Adult Schools - Beresnevičienė, Danguolė (Acta Paedagogica Vilnensia, 1997)
The present paper reveals the investigation data of 370 10th-11th form students (220 among them are studying in adult schools and 150 are studying in general secondary schools), using semantical differential-type scales for the evaluation of their self-concept. Differences of self-concept among these two groups were revealed. The students of adult schools expressed a lower level of self-esteem than students of the same age studying in general secondary schools (with a significant level of 0,005). Especially low was their self-evaluation in the „clever" scale (p < 0,001 ). Non-significant differences of self-concept were obtained regarding the sociometric status when compared to other peers and the structure of the student’s family (a family of intact or divorced parents).